Meningkatkan Pemahaman Membaca Teks Narasi Pada Siswa SMP Advent Menggunakan Strategi Skimming - Aprilia Rosmarie; - Mualimin (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
To gather information, needs a good comprehensive in understanding the information. That’s why the reading activity is important in our life. The researcher conducted a mixed method research and the aims were to investigate the significance improvement and students’ responses after the researcher applied skimming strategy. The researcher analysed both in quantitative and qualitative method. The researcher investigated 7th grader of Adventist School. The focus is about narrative text especially about legend stories such as Tangkuban Perahu, Rawa Pening, Borobudur Temple and Prambanan Temple stories. The researcher concluded and detected a significance improvement in reading skills performed by the students. Result showed that p-value = 0,0110433. The students’ score enhanced and it proved that students could comprehend the narrative text in their reading class.